Van der Knaap disease - Mahata, Manoj Kumar; Ghosh, Saikat; Ghosh, K. C.; Bhattacharya, R.; Mondal, G. P. (International Journal of Research in Medical Sciences, 2019)
Van der Knaap disease is a rare form of leukodystrophy, phenotypically characterized by megalencephaly, early-onset ataxia, pyramidal features, cognitive impairment, with an autosomal recessive inheritence. MRI Brain shows T1 and FLAIR hypointense subcortical cysts in mostly temporal lobes and in fronto-parietal subcortical areas. Authors report a 20 yr. girl with typical features.